A Case of Papillitis in Parry-Romberg syndrome: A Rare Presentation of a Rare Disease (Bangladesh Journal of Neuroscience, 2026)
Progressive Hemifacial Atrophy or Parry-Romberg syndrome (PRS) is a rare idiopathic disease which is characterized by mostly unilateral facial atrophy of the skin and soft tissues. PRS has been associated with various systemic manifestations, particularly neurologic, ophthalmologic and maxillofacial. In the present report, a 16-year-old female patient with hemifacial atrophy and ipsilateral papillitis, accompanied by a short review of literature.